Clinical profile and treatment outcome of patients with spontaneous pneumothorax - Patil, Shivaji V.; Bhagwat, Rajendra V.; Mohite, Rajsinh V.; Barphe, Shailesh S. (International Journal of Research in Medical Sciences, 2017)
Background: The burden of Spontaneous Pneumothorax has been recorded as alarming health problem in medical sciences and is adversely influenced by environmental factors. Objectives of the study were to determine the incidence of spontaneous pneumothorax and to assess the clinical profile and outcome of patients of spontaneous pneumothorax admitted in Government tertiary health care centre. Methods: A hospital based cross-sectional study was conducted in year 2014-15 in the department of Pulmonary Medicine, Government Medical College, Miraj, Maharashtra, India. A total of 2142 patients were admitted with chest complaints during study period were enrolled as study subjects, of which 50 were diagnosed as spontaneous pneumothorax and treated as cases under study. The data were elicited by utilizing structured proforma includes clinical and outcome indicators of Spontaneous Pneumothorax. Qualitative information was computed in tabular and graphical form and analyzed into frequency percentage. Results: Incidence rate of Spontaneous Pneumothorax was 2.33% with higher proportion of cases were belonged male gender (78%) as compared to female (22%). Maximum cases were found in age group, 25-34 years with case ratio of 1:4 for Primary to secondary Spontaneous Pneumothorax. The most common lung disease in secondary spontaneous pneumothorax observed was tuberculosis. Max. 48% cases showed full expansion of lungs followed by 32% with partial expansion with an intervention of appropriate line of management. Conclusions: Tuberculosis is the common cause for secondary spontaneous pneumothorax in India and it should be looked for, in all cases of spontaneous pneumothorax.